2008
DOI: 10.1097/ccm.0b013e318168ea3e
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, randomized, controlled trials evaluating mortality in intensive care: Doomed to fail?

Abstract: This literature search demonstrates that relatively few of the randomized controlled trials conducted in intensive care units and using mortality as a primary outcome show a beneficial impact of the intervention on the survival of critically ill patients. Methodological limitations of some of the randomized controlled trials may have prevented positive results. Other forms of evidence and end points other than mortality need to be considered when evaluating interventions in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(98 citation statements)
references
References 103 publications
4
92
0
2
Order By: Relevance
“…Briefly, a group of physicians, epidemiologists, and statisticians, guided by the 2007 CONSORT (20) (Consolidated Standards of Reporting Trials) statement, Jadad scale (21,22), and prior work and commentaries on the topic (2-5, 10, 14-18, 23), identified RCT elements to be abstracted. We began our search for published RCTs in 2007, as this approximated the end of prior review periods (2,3), and continued our search through May 2013. We examined only RCTs of diagnostic, therapeutic, or process and systems interventions among adult patients conducted in an ICU published in 16 prominent general or critical care journals (see Tables E1 and E2 in the online supplement).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, a group of physicians, epidemiologists, and statisticians, guided by the 2007 CONSORT (20) (Consolidated Standards of Reporting Trials) statement, Jadad scale (21,22), and prior work and commentaries on the topic (2-5, 10, 14-18, 23), identified RCT elements to be abstracted. We began our search for published RCTs in 2007, as this approximated the end of prior review periods (2,3), and continued our search through May 2013. We examined only RCTs of diagnostic, therapeutic, or process and systems interventions among adult patients conducted in an ICU published in 16 prominent general or critical care journals (see Tables E1 and E2 in the online supplement).…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, most published RCTs of critical care interventions that aim to reduce mortality have produced negative results (2)(3)(4)(5), and even these reports may be overly optimistic because negative trials are less likely to be published and identified. Although several RCTs have revolutionized critical care practice (6)(7)(8), the results of critical care trials on the whole have been so disappointing that some leaders in the field have suggested a renewed focus on nonexperimental study designs (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…34 The complexity of critical illness and ICU interventions renders them extremely difficult to study in a reasonably controlled fashion, and mechanistic interventions in these patients seem unlikely to produce a measurable impact. For ALI and other hospital-acquired conditions, enrollment of patients in clinical trials after the onset of organ failures and critical illness syndromes limits available interventions to state-of-the-art supportive care.…”
Section: Limitations Of Interventional Trials In Critical Carementioning
confidence: 99%
“…Unfortunately, more than 30 years of extensive clinical research resulted in mainly non-significant results. According to a recent review of 72 prospective randomised trials with mortality being the primary endpoint, 55 ended up with non-significant results, also including several studies on adjuvant therapies [4,5]. Promising positive results of single-centre studies were often contradicted later by large multicentre trials [5].…”
Section: Introductionmentioning
confidence: 99%